Practical Issues in Monitoring a Hydrocarbon Cultivation Activity in Italy: The Pilot Project at the Cavone Oil Field - Zaccarelli, Lucia; Anselmi, Mario; Vassallo, Maurizio; Munafò, Irene; Faenza, Licia; Sandri, Laura; Garcia, Alexander; Polcari, Marco; Pezzo, Giuseppe; Serpelloni, Enrico; Anderlini, Letizia; Errico, Maddalena; et al. (Frontiers in Earth Science, 2021)
In this paper we describe the results of an experimental implementation of the recent guidelines issued by the Italian regulatory body for monitoring hydrocarbon production activities. In particular, we report about the pilot study on seismic, deformation and pore pressure monitoring of the Mirandola hydrocarbon cultivation facility in Northern Italy. This site hosts the Cavone oil field that was speculated of possibly influencing the 2012 ML 5.8 Mirandola earthquake source. According to the guidelines, the monitoring center should analyse geophysical measurements related to seismicity, crustal deformation and pore pressure in quasi real-time (within 24-48 hours). A traffic light system would then be used to regulate underground operations in case of detecting significant earthquakes (i.e. events with size and location included in critical ranges). For these two-year period of guidelines experimentation, we analysed all different kinds of available data, and we tested the existence of possible relationship between their temporal trends. Despite the short time window and the scarce quantity of data collected, we try to performed the required analysis and extracted as much meaningful and statistically reliable information from the data. We discuss here the most important observations drawn from the monitoring results, and highlight the lessons learned by describing practical issues and limitations that we have encountered in carrying out the tasks as defined in the guidelines. Our main goal is to contribute to the discussion about how to better monitor the geophysical impact of this kind of anthropogenic activity. We point out the importance of a wider seismic network but, mostly, of borehole sensors to improve microseismic detection capabilities. Moreover, the lack of an assessment of background seismicity in an unperturbed situation -due to long life extraction activities- makes it difficult to get a proper picture of natural background seismic activity, which would be instead an essential reference information for a tectonically-active regions, such as Northern Italy.